MEMBACA DEMOKRASI DELIBERATIF JURGEN HABERMAS DALAM DINAMIKA POLITIK INDONESIA - Mohammad Asy'ari Muthhar (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2016)
Democracy is a government based on popular sovereignty. This definition implies all matters relating to the welfare of the majority must be based on the will of the people in general and not based on the desire of a handful of people. The problems that occurred during precisely the parameters of democracy only stop the implementation of the general election. Almost never been discussed whether the policies made by the government already represents the wishes of the people or not. It seems that occurred during this time, in Indonesia, the policy made only prioritize the interests of a few people, or to order certain parties. This view departs from the reality of what happened, when the government issued a policy is often criticized on the people. This condition as a result of the lack of space for people to participate in policy formulation, there is no interaction or communication between people and state. In fact, the interaction in a democracy such as Indonesia is very important that the founding purpose of government reached. These interactions are by Jurgen Habermas termed deliberative democracy.